Regulation of the Mdm2-p53 signaling axis in the DNA damage response and tumorigenesis - Carr, Michael I. (Transl Cancer Res, 2016)
The p53 tumor suppressor acts as a guardian of the genome in mammalian cells undergoing DNA double strand breaks induced by a various forms of cell stress, including inappropriate growth signals or ionizing radiation. Following damage, p53 protein levels become greatly elevated in cells and p53 functions primarily as a transcription factor to regulate the expression a wide variety of genes that coordinate this DNA damage response. In cells undergoing high amounts of DNA damage, p53 can promote apoptosis, whereas in cells undergoing less damage, p53 promotes senescence or transient cell growth arrest and the expression of genes involved in DNA repair, depending upon the cell type and level of damage. Failure of the damaged cell to undergo growth arrest or apoptosis, or to respond to the DNA damage by other p53-coordinated mechanisms, can lead to inappropriate cell growth and tumorigenesis. In cells that have successfully responded to genetic damage, the amount of p53 present in the cell must return to basal levels in order for the cell to resume normal growth and function. Although regulation of p53 levels and function is coordinated by many proteins, it is now widely accepted that the master regulator of p53 is Mdm2. In this review, we discuss the role(s) of p53 in the DNA damage response and in tumor suppression, and how post-translational modification of Mdm2 regulates the Mdm2-p53 signaling axis to govern p53 activities in the cell.